1990 Approved budget estimates of the Government of the Plateau State of Nigeria (Jos : Government of Plateau State of Nigeria, 1990)
This is the Plateau State 1990 budget proposal tagged "The Budget of Consolidation, presented to the Plateau State House of Assembly by the Plateau State governor, Lt. Col. A.A. U. Kama in 1990.
osa 4/2/19
Loans
Keywords: Economic Planning; Economic Planning -- Plateau State; Budget; Economic Planning and Budget; Plateau